2020
DOI: 10.13106/jafeb.2020.vol7.no9.517
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Service Quality and Perceived Value on Customer Satisfaction and Behavioral Intentions: Evidence from Convenience Stores in Vietnam

Abstract: This research investigates the relationship among product quality, service quality, perceived value, customer satisfaction, and behavior intentions. Validated measurements were identified from a literature review. The measurement model and the conceptual model depicting hypothesized relationships were evaluated based on responses from 220 customers using confirmatory factor analysis and structural equation modeling. The testing results show that, for the direct path, product quality has a significant, positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
50
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 40 publications
10
50
0
2
Order By: Relevance
“…Regarding loyalty to the destination, numerous works analyze the behavior of tourists based on their loyalty [109][110][111][112][113][114][115]. Authors such as Lee [116] showed that the destination image indirectly affects loyalty, that in this case, it is the new destination image generated after the trip that provides all the influence.…”
Section: Hypothesis 2b (H2b) Image Has a Positive Influence On New Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding loyalty to the destination, numerous works analyze the behavior of tourists based on their loyalty [109][110][111][112][113][114][115]. Authors such as Lee [116] showed that the destination image indirectly affects loyalty, that in this case, it is the new destination image generated after the trip that provides all the influence.…”
Section: Hypothesis 2b (H2b) Image Has a Positive Influence On New Imagementioning
confidence: 99%
“…Do you plan to visit the province again another time? [109][110][111][112][113][114][115] A pre-test of this questionnaire was performed on 50 people who had visited the province and stayed in a rural tourism establishment. This was done to evaluate whether the scales were well constructed and the multiple questions on the questionnaire were understood.…”
Section: Loyalty (Loy)mentioning
confidence: 99%
“…For instance, the expectancy-disconfirmation principle underpins the service quality definition, closely related to customer satisfaction (Parasuraman, Zeithaml, & Berry, 1985). Grönroos (1982) and Tran and Le (2020) illustrated that service quality affects the importance of an experience, the quality of a partnership, and the likelihood of purchasing. Despite the significant consequences for administrators, researchers, customers, service efficiency, experience meaning, interaction quality, and action motives, they are all poorly understood in current literature.…”
Section: Introductionmentioning
confidence: 99%
“…This research integrates HEdPERF with the traditional two-dimensional model of service quality to merge general and context-based viewpoints, detect the effects on student satisfaction of technical and functional service quality, and the relations between HEdPERF and two dimensions of service quality. Tran and Le (2020) found that the quality of service affects the importance of customer experience, the strength of a partnership, and the likelihood of making a purchase. Despite the critical implications for management, academics, and customers, service efficiency, experience meaning, interaction quality, and action motives are all poorly understood in current literature.…”
Section: Introductionmentioning
confidence: 99%
“…The construct of contentment has entered the marketing area (Lee & Seong, 2020). Prior research indicates that consumers' absolute behavioral intentions emanate from their satisfaction, while at the same time satisfaction is the outcome of proficient and decent service quality (Tran & Le, 2020).…”
Section: Introductionmentioning
confidence: 99%